The efficacy and safety of double (cepeginterferon alfa-2b and ribavirin) and triple (simeprevir, cepeginterferon alfa 2b and ribavirin) treatment regimens in chronic hepatitis C patients. The experience of everyday clinical practice - N. P. Blokhina; E. A. Nurmuhametova; M. G. Rusanova; I. V. Gagarina; E. S. Mar’jamova; N. A. Kuznetsova; T. V. Mar’janovskaja; T. V. Lopatina; O. V. Kuzina; I. N. Alekseeva; E. N. Shurenkova; A. V. Devjatkin; et al. (Журнал инфектологии)
The objective. To evaluate the efficacy, safety and tolerability of double (cepeginterferon alfa-2b and ribavirin) and triple (simeprevir, cepeginterferon alfa 2b and ribavirin) treatment regimens in chronic hepatitis C patients in everyday clinical practice of the Hepatology Center in Clinical Infectious Diseases Hospital in Moscow.Materials and methods. From 2013 to 2015 a total of 289 patients with chronic hepatitis C received antiviral therapy with cepeginterferon alfa 2b. 267 patients received combination of cepeginterferon alfa 2b and ribavirin. 22 patients received triple antiviral therapy with simeprevir, cepeginterferon alfa 2b and ribavirin. Treatment efficacy was assessed by the rate of sustained virologic response on 12/24 week after completion of antiviral therapy (SVR 12/24). In safety analysis all 289 patients were included. All cases of deterioration of the patient’s condition and laboratory abnormalities were registered throughout the treatment period and follow up.Results. 267 patients (74,5%, n=199, with 2/3 genotype, 25,5%, n = 68, with 1 genotype) received cepeginterferon alfa 2b 1,5 µg/kg/week and ribavirin 800-1400 daily (weight based). 22 patients with genotype 1 (the majority of them had advanced fibrosis (F3-F4) underwent triple therapy with simeprevir 150 mg once daily in combination with cepeginterferon alfa 2b 1,5 µg/kg/week and ribavirin 800-1400 mg daily (weight based) for 12 weeks, followed by cepeginterferon alfa 2b/ ribavirin therapy for 12-36 weeks. SVR was observed in 85,6% (n=113) of genotype 2/3 infected patients and in 64,6% (n=31) of genotype 1 infected patients. Among patients with mild or moderate fibrosis SVR rate was 90,7% in genotype 2/3 patients and 75% in genotype 1 patients. 21 patient completed the course of triple therapy. SVR was observed in 71,4% (n=15) of patients. Registered adverse reactions were common for interferon/ribavirin based therapy. In most cases adverse events were moderate and matched grade 1-2 of CTCAE.Conclusion. The present experience confirms the efficacy and safety of double therapy including cepeginterferon alfa 2b and ribavirin in genotype 1 and 2/3 infected patients. The use of this regimen is reasonable in patients who don’t have negative predictive factors of response to interferon-based therapy. In patients with genotype 1 HCV and/or advanced fibrosis (F3-F4) adding of simeprevir to the cepeginterferon alfa/ribavirin combination reduces the duration of treatment, improves the efficacy, while maintaining a good safety profile.